2017
DOI: 10.5897/jdoh2016.0216
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of obesity among preschool children and its relation with dental caries

Abstract: There is increasing interest in investigating the association between dental caries and childhood obesity, particularly among preschoolers where the evidence is limited. We aimed to measure the prevalence of obesity/overweight among preschool children aged 3 to 6 years, and to determine the relationship between obesity and dental caries in the primary dentition. A cross-sectional study was carried out in eight public and private preschools using a multi-stage stratified sample of 820 children. Waist circumfere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…This review found no convincing evidence to demonstrate a specific association between obesity and dental caries in the primary dentition when compared to the permanent dentition. Despite the limited evidence, it appears that more studies tend to show that young children with dental caries in the primary dentition are underweight compared to children without caries, which is an inverse association [14, 1820]. Obese older children and adolescents are more likely to have dental caries in their permanent teeth, which is a positive association [3335].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This review found no convincing evidence to demonstrate a specific association between obesity and dental caries in the primary dentition when compared to the permanent dentition. Despite the limited evidence, it appears that more studies tend to show that young children with dental caries in the primary dentition are underweight compared to children without caries, which is an inverse association [14, 1820]. Obese older children and adolescents are more likely to have dental caries in their permanent teeth, which is a positive association [3335].…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation for the inverse association might be that children with untreated caries could experience pain and infection, thus preventing them from consuming adequate nutrition. In addition, other factors that contribute to overall wellbeing could be affected, including the ability to sleep, which in turn may lead to malnutrition and growth impairment [12, 18, 20, 25, 36]. The wider literature suggests that underweight children gained weight after receiving dental treatment [19, 50].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations